Study of Two-Phase Nonlinear Advection Dispersion Model for Displacement Washing of Porous Particles Using OCFE with Lagrangian Basis - Arora, Shelly; Alemar, Dereje Alemu; Potůček, František (My University, 2020)
A comprehensive diffusion dispersion model has been presented for displacement washing of porous particles. Model equations have been divided into two phases, namely bulk fluid phase and particle phase. Both the phases have been characterized by particle geometry and pore radius of particles. Inter-pore and intra-pore solute concentrations have been related to Langmuir adsorption isotherm. Nonlinear set of model equations has been solved by using the technique of orthogonal collocation on finite elements with Lagrangian basis. Effect of different parameters such as Péclet number, bed porosity and distribution ratio has been shown graphically via breakthrough curves and surface plots. Stability of the numerical technique has been checked by L2 and L∞ norms for different values of parameters. Validity of the model on the laboratory-scale washer has been verified by comparing experimental and model-predicted values. Applicability of the model has also been discussed through industrial parameters.
Studie dvoufázového nelineárního disperzního modelu vytěsňovacího praní porézních částic pomocí metody OCFE s Lagrangeovým základem
Keywords: orthogonal collocation; axial dispersion coefficient; Péclet number; bed porosity; pore radius of particles; particle geometry; ortogonální kolokace; axiální disperzní koeficient; Pécletovo kritérium; mezerovitost vrstvy; poloměr pórů částice; geometrie částice